Pengaruh Penambahan Dosis Koagulan Terhadap Parameter Kualitas Air dengan Metode Jartest - Nur Ihda Farikhatin Nisa; Achmad Aminudin (JRST (Jurnal Riset Sains dan Teknologi), 2019)
Water is one of the important components of human life or other living things. With the increasing number of residents, the need for clean water has also increased. However, this increase in demand is not offset by the availability of clean water due to the lower quality of water produced by the water treatment plant. Therefore, it is necessary to do alternative water treatment so that clean water needs can be sufficient. One method of processing clean water that can be done is the Jar test method. This study aims to determine the effect of coagulant dose addition on water quality parameters including pH, turbidity, TDS and total hardness of the Manisrejo City Madiun well water sample after water treatment. The research method is carried out through three stages, namely the preparation stage, the instrument analysis stage and the experimental stage. Where the type of coagulant used is Poly Aluminum Chloride (PAC). From the research that has been done, the optimum PAC coagulant dose is 43 mg / l. The conclusion obtained in this study is that the greater the coagulant dose added to the water sample, the smaller the pH value, the value of turbidity, the TDS value and the total hardness of the water sample.